Optimal Policy and Non-Scale Growth with R&D Externalities - Simone Valente (ETH Zurich, CER-ETH - Center of Economic Research, 2009)
An established result of the endogenous growth literature is that competitive equilibria in expanding-varieties models are suboptimal due to the rent-effect: monopolistic pricing drives the equilibrium quantity of each intermediate below the efficient level, implying that it is optimal to subsidize final producers. This paper shows that, if scale effects are eliminated by including R&D spillovers in the model, normative prescriptions change. Since the laissez-faire economy under-invests into R&D activity, the share of resources devoted to intermediates' production increases, and this reallocation effect contrasts the rent-effect. In many scenarios, including the polar case of logarithmic preferences, the reallocation effect surely dominates: the equilibrium quantity of each intermediate exceeds the optimal one, and the optimal policy consists of taxing final producers because fiscal authorities must internalize the overshooting mechanism generated by under-investment in R&D.
Keywords: O41; O31; 330; Endogenous Growth; Scale Effects; R&D Externalities; Optimal Policy; Optimales Wachstum; Skalenertrag; Forschung; Externer Effekt; Endogenes Wachstumsmodell